Profile analysis and hospitalization outcomes in critically ill patients with pressure ulcers - Santos, Isabela Gomes Musa dos; Beatriz; Fernandes , Henrique Mateus; Balestra , Natalia; Barbado , Karoline Razimavicius; Ramalho , Aline de Oliveira (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To describe the clinical profile of patients who developed pressure ulcers (PU) during intensive care in a cardiology unit and to identify the factors associated with discharge and death outcomes. Method: Observational, retrospective cohort study. Patients who developed PU during their stay in the intensive care units (ICUs) of a philanthropic hospital in São Paulo and were recorded in the database from January 2018 to June 2020 were included. The study was approved by the institution’s Research Ethics Committee. Fisher’s Exact Test, Student’s t-test, and Pearson’s ꭓ2 test were used to assess the associations, with a significance level of 0.05. Results: Among 456 critically ill patients evaluated, 51 developed PU in the ICU, with a prevalence of 11%. The sample consisted of 84.3% male patients, with a mean age of 75.8 years (SD=13.6). Sacral PU were present in 70.5% of the cases. Nutritional risk, SAPS 3 score, length of ICU stays, capillary refill time, age, and RASS score showed significant correlations with death as an outcome. Conclusion: Clinical factors correlated with death outcomes were identified in critically ill patients who developed PU in the ICU. As a clinical implication, the findings highlight the importance of guiding care teams to implement targeted care strategies for these patients.